RESPON PERTUMBUHAN DAN HASIL TANAMAN SELEDRI AKIBAT PEMBERIAN BOKASHI KAYAMBANG DAN ABU DI TANAH GAMBUT (Respond of Celery Growth and Yield in Consequence of Application of Kayambang Bokashi and Ash In Peatland) - Kresnatita, S1), Kresnatita, S1) (Universitas Palangka Raya, 2017)
ABSTRACTApplication of kayambang bokashi (Salvinia molesta) and ash in peatland was a way to improvethe environment of growth. Bokashi was used as fertilizer to produce variety of advantageousmicrobe population in soil so the growth of disadvantageous pathogens were inhibited, and alsoto increase the nutrient availability. Ash contain few essential nutrients for growth, development,and yield of plant. Application of ash in peatland was profitable to increase soil pH, add Ca andMg, enchance the availability of P and Mo, reduce the toxication of Fe, Mn and Al, also toimprove the existence of microorganisms in soil. The use of burnt ash of plant litter combustionin agriculture have been performed, whether to neutralize the soil acidity or as fertilizer. Theaim of this study was to know the respond of celery growth and yield in peatland by givingkayambang bokashi and ash treatment. This study was performed for 4 months in Jl. DohoKalampangan Village, Sabangau Districts, Palangka Raya City. This study used Factorial ofCompletely Random Design with 2 treatment factors. First factor was kayambang bokashitreatment (K) divided into 5 treatment levels, those were K0= without bokashi ; K1= 10 t.haË1(141 g.polybag) ; K2= 20 t.haË1 (282 g.polybag) ; K3= 30 t.haË1 (423 g.polybag) and K4= 40t.haË1 (564 g.polybag),wereas the second factor was ash treatment (B) divided into 4 treatmentlevels,those were B0 = without ash ; B1 = Ash 10 t.haË1 (141 g.polybag-1) ; B2= Ash 20 t.haË1(282 g.polybag-1) ; B3= Ash 30 t.haË1 (423 g.polybag-1) and B4= Ash 40 t.haË1 (564 g.polybag).The result of this study showed that there were interaction between treatment of kayambangbokashi and ash on growth parameter of plant height aged 10 and 12 weeks after planting,number of leaves aged 8, 10, and 12 weeks after planting, also the fresh weight of root atharvest. There was significant difference of plant height parameter aged 2, 4, 6, and weeks afterplantng, also fresh weight of stover in consequence of single treatment of kayambang bokashiand ash. There was significant difference of leaves number parameter aged 4 and 6 weeks afterplanting in consequence of single treatment of kayambang bokashi. There was no significantdifference of celeryâs number of leaves in 2 weeks after planting. The best treatment wasapplication of kayambang bokashi dose of 40 t.haË1 and ash at dose of 30 t.haË1 (K4B3).Keywords: Kayambang bokashi, ash, peatland, celery (Apium graveolens L.)